2015
DOI: 10.5958/0974-0279.2015.00005.1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Forecasting of Price Volatility: An Application of GARCH and EGARCH Models

Abstract: This paper has studied the autoregressive integrated moving-average (ARIMA) model, generalized autoregressive conditional heteroscedastic (GARCH) model and exponential GARCH (EGARCH) model along with their estimation procedures for modelling and forecasting of three price series, namely domestic and international edible oils price indices and the international cotton price 'Cotlook A' index. The Augmented Dickey-Fuller (ADF) and Philips Peron (PP) tests have been used for testing the stationarity of the series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 10 publications
1
26
0
5
Order By: Relevance
“…Accordingly, using a model which can help to measure the volatility of price indexes (Engle 1982, Zakoian 1994, Bollerslev 1986, Zakoian 1994 serves as an insight to predict volatility. In line with this, Lama et al (2015), Le Roux (2018), and Adugh ( 2019) are pioneers who model volatility specifically on agricultural commodity prices.…”
Section: Statement Of the Problemmentioning
confidence: 95%
See 1 more Smart Citation
“…Accordingly, using a model which can help to measure the volatility of price indexes (Engle 1982, Zakoian 1994, Bollerslev 1986, Zakoian 1994 serves as an insight to predict volatility. In line with this, Lama et al (2015), Le Roux (2018), and Adugh ( 2019) are pioneers who model volatility specifically on agricultural commodity prices.…”
Section: Statement Of the Problemmentioning
confidence: 95%
“…According to Lama et al (2015), most of the agricultural price series can be modeled as time series data where the information is collected over time at equal time-epochs. In this framework, Lama et al (2015) studied the autoregressive integrated moving average (ARIMA) model, generalized autoregressive conditional Heteroskedastic (GARCH) model and exponential GARCH (EGARCH) model along with their estimation procedures for modeling and forecasting of three price series, specifically domestic and international edible oils price indices and the international cotton price 'Cotlook A' index. Their study revealed that the EGARCH model outperformed the ARIMA and the GARCH models in forecasting the international cotton price series primarily due to its ability to capture asymmetric volatility patterns.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…First, unlike the relatively few previous studies done in Tanzania (see for example, Mutaju and Dickson (2019)), we apply both GARCH and the EGARCH models to capture both symmetry and asymmetry effects, and determine key characteristics of DSE stock returns. Secondly, unlike Mutaju and Dickson (2019) we divide our data set into three periods, namely; the period between 2014 and 2019, the period before "General Election" (2014-2015) and after "General Election" of 2015-2019. We believe this categorization of period is important because change of power by those in government may influence investor's participation in the stock market through the adoption of "wait and see" attitude (Nancy, 2016) and this might have remarkable consequences on the behavior of stock prices.…”
Section: Asian Journal Of Economic Modellingmentioning
confidence: 99%
“…The motivation for undertaking this exercise is two folds. First, although much has been documented on the volatility of stock prices elsewhere in the world, relatively little is known in the context of Tanzania (see for example, (Achal, Girish, Ranjit, & Bishal, 2015;Ajaya & Swagatika, 2018;Akhtar & Khan, 2016;Mathur, Chotia, & Rao, 2016)). Existing studies that have attempted to examine volatility within the context of GARCH models in Tanzania have mainly focused on other macroeconomic variables such as inflation (Edward, Eliab, & Estomih, 2004) exchange rate (Carolyn, Betuel, & Pitos, 2018;Epaphra, 2016) tax revenues (Chimilila, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…An EGARCH model was chosen in view of certain advantages it has. In addition to the GARCH model of Bollerslev (1986) to estimate conditional volatility, the EGARCH model allows for the asymmetric effects between positive and negative shocks on the conditional variance (Lama, Jha, Paul, & Gurung, 2015). Nelson and Cao (1992) suggest that whereas there are non-negativity constraints on the parameters of the process in the GARCH model of Bollerslev (1986), there are no restrictions on the parameters in the EGARCH model.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%